Geochemical evolution of groundwater in a basaltic aquifer based on chemical and stable isotopic data: Case study from the Northeastern portion of Serra Geral Aquifer, São Paulo state (Brazil) - Gastmans, Didier [UNESP]; Hutcheon, Ian; Menegário, Amauri Antônio [UNESP]; Chang, Hung Kiang [UNESP] (Elsevier, 2016)
Groundwater from the fractured basalt Serra Geral Aquifer (SGA) represents an important source for water supply in Northeastern São Paulo state (Brazil). Groundwater flow conditions in fractured aquifers hosted in basaltic rocks are difficult to define because flow occurs through rock discontinuities. The evaluation of hydrodynamic information associated with hydrochemical data has identified geochemical processes related to groundwater evolution, observed in regional flowpaths. SGA groundwaters are characterized by low TDS with pH varying from neutral to alkaline. Two main hydrochemical facies are recognized: Ca-Mg-HCO3, and Na-HCO3 types. Primarily, the geochemical evolution of SGA groundwater occurs under CO2 open conditions, and the continuous uptake of CO2 is responsible for mineral dissolution, producing bicarbonate as the main anion, and calcium and magnesium in groundwater. Ion exchange between smectites (Na and Ca-beidelites) seems to be responsible for the occurrence of Na-HCO3 groundwater. Toward the Rio Grande, in the northern portion of the study area, there is mixing between SGA groundwater and water from the sandstones of the Guarani Aquifer System, as evidenced by the chemical and isotopic composition of the groundwater. Inverse mass balance modeling performed using NETPATH XL produces results in agreement with the dissolution of minerals in basalt (feldspars and pyroxenes) associated with the uptake of atmospheric CO2, as well as the dissolution of clay minerals present in the soil. Kaolinite precipitation occurs due to the incongruent dissolution of feldspars, while Si remains almost constant due to the precipitation of silica. The continuous uptake of CO2 under open conditions leads to calcite precipitation, which in addition to ion exchange are responsible by Ca removal from groundwater and an increase in Na concentrations. Down the flow gradientCO2 is subject to closed conditions where the basalts are covered by the sediments of Bauru Group or associated with deeper isolated discontinuities. A decrease in the amount of dissolution of labradorite and augite is observed, associated with precipitation of carbonates and kaolinite. Stable isotope ratios of SGA groundwater vary from -37.8‰ to -61.3‰ VSMOW for δ2H VSMOW, and -5.7‰ to -8.9‰ VSMOW for δ18O, indicating temporal variations in climatic conditions during recharge.
Keywords: Basalts; Brazil; Hydrochemistry; Netpath XL; Stable isotopes; Water-rock interaction